Politik Hukum Putusan MK No. 46/PUU-VIII/2010 sebagai Upaya Pembangunan Hukum Nasional - Yazid Bustomi (Penerbit Goodwood, 2023)
Purpose: To identify the Constitutional Court's decision No. 46/PUU-VIII/2010 regarding the recognition of the status of children out of wedlock, has reflected the form of development of national law or not. Methodology: This legal research is a normative research with statutory, conceptual and case approaches conducted by examining primary and secondary legal materials. Results: Constitutional Court's decision No. 46/PUU-VIII/2010 has fulfilled the rules of good legal politics because this decision can maintain complete unity, both territory and ideology that is built democratically so that it is able to create social justice and there is no exclusivity in the decision against one of the religions in Indonesia. This decision is a manifestation of the development of Indonesian law which is capable of dealing with the phenomenon of children born out of wedlock in terms of providing protection and legal certainty for children born outside of wedlock status, by combining Islamic law and national law (so that the formation of this decision is not based on one religion only), then from the combination of the two laws can form a new law that can meet the needs of society as a means of development that is certain and justice. Limitations: This research is limited to reviewing the decisions of the constitutional court regarding the recognition of the status of children out of wedlock which are analyzed by development law theory.